Aplikasi Tenologi Metode Topikal Pada Pemijahan Ikan Nila Sebagai Upaya Produksi Benih - Nursanti Abdullah; M.Abjan Fabanyo (Jurnal Pengabdian Magister Pendidikan IPA, 2021)
Topical method technology is one of the methods that is trying to be developed to stimulate spawning and can overcome stress in small fish. The purpose of PKM is to help partner groups and local communities to produce their own seeds. From this PKM activity, it has been proven that partner groups and local communities have succeeded in spawning fish with the application of Topical method technology. From several treatments that were tested with TMT and hormones as stimulants, fish spawned with a degree of ovulation of 85% and SR larvae for 7 days of observation of 75%.